Antibacterial Properties of Nano-Layered Au, Ag and Al Film Coatings on Flexible Organic Substrates - Pat, Zerrin; Sanci, Ozlem; Yuksel, Huseyin; Pat, Suat (Asian Journal of Chemistry, 2014)
The antibacterial properties of a surface are important for the health industry. Gold, silver and aluminium nano-layers were coated using a metal plasma vacuum arc on flexible organic substrates. The antibacterial properties of the coated nano-layered metal films were examined using E. coli (ATCC 25922) bacteria. The contact time of the bacteria solutions (109 CFU/mL) to the nano-layered metal coatings was adjusted to 3 h in the experimental procedures. The antibacterial properties of the coated and uncoated samples were determined after 24 h. The obtained results show that the antibacterial properties of the nano-layered metal film coatings on flexible organic substrates were improved. The antibacterial effect is determined as Ag > Au > Al. In addition, the surface roughness and the surface free energies of the coated samples were determined. The produced coatings showed the antibacterial property.